2020
DOI: 10.3390/nu12041005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Modified Extracts of the Microalga Planktochlorella nurekis Attenuates the Development of Stress-Induced Senescence in Human Skin Cells

Abstract: More recently, we have proposed a safe non-vector approach to modifying the biochemical profiles of the microalga Planktochlorella nurekis and obtained twelve clones with improved content of lipids and selected pigments and B vitamins and antioxidant activity compared to unaffected cells. In the present study, the biological activity of water and ethanolic extracts of modified clones is investigated in the context of their applications in the cosmetic industry and regenerative medicine. Extract-mediated effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The samples were then incubated at 37 °C for 24 h with shaking (1000 RPM) and centrifuged (12,000 RPM, RT, 10 min). Supernatants were collected and stored until use at −20 °C [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were then incubated at 37 °C for 24 h with shaking (1000 RPM) and centrifuged (12,000 RPM, RT, 10 min). Supernatants were collected and stored until use at −20 °C [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the results obtained in the in vitro CAM assay, both EA and HP from Chlorella sorokiniana microalgae showed interesting angiogenic potential, although there are very little data on the effect of extracts or biomolecules derived from microalgae on vessel development. Some authors such as Jarquín-Cordero et al have demonstrated the ability of the microalga Chlamydomonas reinhardtii to express proangiogenic growth factors [51][52][53][54]. Therefore, in the context of the activity of the extracts on tumors, these results should be evaluated with new assays.…”
Section: Discussionmentioning
confidence: 99%
“…Given this new paradigm of photocarcinogenesis involving dermal fibroblast senescence with resultant IGF-1 deficiency, therapeutics designed to prevent or treat fibroblast senesce could have use, especially in populations at high risk for skin cancer. Examples of agents currently studied for abilities to inhibit fibroblast senescence include extracts of microalga [37] or Akebia quinate fruit [38]. Additionally, Cr supplementation protects against mitochondrial mutagenesis as well as increases in matrix metalloproteinase-1 in response to UVA [39].…”
Section: Discussionmentioning
confidence: 99%